Analysis of Sports Education Students Interest in Muhammadiyah University of Surakarta in Archery Sports - Alfin Wahyu Nugroho; Gatot Jariono (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Archery, namely archery, is a static sport that requires good physical condition, including strength and endurance, especially in the upper body muscles.  The purpose of  the researchers was to find out how interested students are and how important sports are for students of Sports Education  at the University of Muhammadiyah Surakarta. A sample is part of the number and characteristics possessed by that population. The study took samples on Sports Education students of  Muhammadiyah University of Surakarta semester 1 which totaled 89. Based on the results and discussion of the data obtained, researchers can draw conclusions about the interest of Sports Education students of the University of Muhammadiyah Surakarta in  archery, and that the interest of  Sports Education  students  of  the University of Muhammadiyah Surakarta  in archery sports is low. It is proven that only 7.5%  of Sports Education students of  Muhammadiyah University of Surakarta chose to strongly agree. There are several indicators of the reasons why students of Sports Education  at the University of Muhammadiyah Surakarta  have a low interest in archery, namely in the question of the body to be healthy and fit, refresh the brain, and want to excel in archery sports 38.3 students of Sports Education   of Muhammadiyah University of Surakarta choose to hesitate.